Gambaran tingkat kecemasan orang tua dengan Anak Berkebutuhan Khusus (ABK) dan penanganannya di UPTD PSBK Provinsi Sulawesi Tenggara - Annisa, Rizki; Opod, Hendri; Sinolungan, Jehosua Samratson Victor (Jurnal Kedokteran Komunitas dan Tropik, 2024)
According to 2021 data, the number of Indonesia children with autism has increased to 2.4 million. Government established the UPTD Autism Service Centre (PLA) which handle early age autism therapy, which later changed to UPTD for Handling Children with Special Needs (PSBK) which broaden to early age children with special needs. However, the long therapy period (6 months to 5 years), limited therapist staff, and limited equipment creating a long queue therapy service, has caused anxiety among parents of Children with Special Needs (ABK). This was a descriptive quantitative method research with univariate data analysis techniques, with univariable: "anxiety". We used observation, interview and documentation techniques to collect data. The primary subjects were parents of ABK at UPTD PSBK Southeast Sulawesi Province. Secondary data is obtained from library materials, literature, previous research, books, journals, and so on. We described the processed data by using tabulation.. The research showed that the anxiety of the parents was predominantly at a moderate level of anxiety, namely 47%. Moderate levels of anxiety tend to make individuals selective and alert. From the results of this research, researchers provide suggestions for parents to manage their stress so that it does not cause anxiety which can have a negative impact on parents, children and family/relatives around them. The UPTD institution for Handling Special Needs Students (PSBK) of Southeast Sulawesi Province may consider to increase the number and the quality of the therapists. This may help in shortening the duration of queuing, having more hours of therapy and making better performance institution. Keywords: anxiety, parents, children with special deeds, UPTD PSBK